2010
DOI: 10.1111/j.1944-9720.2010.01102.x
|View full text |Cite
|
Sign up to set email alerts
|

Three A's: How Do Attributions, Attitudes, and Aptitude Contribute to Foreign Language Learning?

Abstract: The researchers investigated attributions for success, attitudes, and aptitudes for native language learning and foreign language learning success for 648 students enrolled in 100‐level university foreign language courses (Spanish, French, and German). We examined relationships via correlational analyses and used structural equation modeling to determine the best predictive model. Relationships among variables were generally positive but low to moderate in magnitude (r=−.12 to r=.45).The best predictive model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…In the 2000 study mentioned above, Donato et al sought to “create a profile” where items including attitudes and self‐assessment could be related to individual achievement (Donato et al, , p. 386). Cochran, McCallum, and Bell () similarly included students’ attributions for their own success and their attitudes toward learning a language, examining their relationship through the quantitative analysis of Structural Equation Modeling with the students’ achievement. Other studies have been more focused on perceptions of the learning situation specifically, linking perceptions of corrective feedback with their desire to participate (Yoshida, ), perceptions of certain instructional techniques with their choice of learning strategies (Mori & Shimizu, ), or perceptions of instructors with their motivation or anxiety (Ewald, ; Wesely, ).…”
Section: The Trait or Learner Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2000 study mentioned above, Donato et al sought to “create a profile” where items including attitudes and self‐assessment could be related to individual achievement (Donato et al, , p. 386). Cochran, McCallum, and Bell () similarly included students’ attributions for their own success and their attitudes toward learning a language, examining their relationship through the quantitative analysis of Structural Equation Modeling with the students’ achievement. Other studies have been more focused on perceptions of the learning situation specifically, linking perceptions of corrective feedback with their desire to participate (Yoshida, ), perceptions of certain instructional techniques with their choice of learning strategies (Mori & Shimizu, ), or perceptions of instructors with their motivation or anxiety (Ewald, ; Wesely, ).…”
Section: The Trait or Learner Orientationmentioning
confidence: 99%
“…The possibility cannot be ruled out that students who have higher proficiency, perhaps as a result of an unknown or unmeasured variable like access to better learning strategies or members of the target community, then have higher self‐efficacy. Finally, scholars should embrace when a relationship is not found when expected, and they should allow themselves to explore and interpret the reasons (see for instance the study by Cochran et al, ). This is a perspective that is currently lacking in educators’ understanding of learner attitudes, perceptions, and beliefs.…”
Section: The Trait or Learner Orientationmentioning
confidence: 99%
“…At the same time, numerous scholars have recently documented positive attitudes toward foreign language (FL) study in the United States, both among students and in the population in general. For example, Cochran, McCallum, and Bell () and Martin () at the university level and Acheson, Nelson, and Luna () at the high school level all found that FL students’ self–reported attitudes were mostly positive. Likewise, Rivers et al.…”
mentioning
confidence: 99%
“…Many previous studies have indicated that gender differences have an influence on learning styles (e.g., Allakbari and Tazik 2011;Grenfell and Harris 2012), and learning performance (e.g., Cochran et al 2010). Learners' gender is one of factors that affect learning; therefore, this factor should be considered in future studies on language learning.…”
Section: Resultsmentioning
confidence: 97%